2011
DOI: 10.1007/s00127-011-0416-2
|View full text |Cite
|
Sign up to set email alerts
|

A new psychological intervention: “512 Psychological Intervention Model” used for military rescuers in Wenchuan Earthquake in China

Abstract: "512 PIM" was an effective psychological intervention for military rescuers in reducing symptoms of PTSD, anxiety and depression after a crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Nineteen studies assessed the impact of non-specific “debriefing”—although the procedures and the focus of the intervention differed between studies. In 11 (58%), debriefing had positive gains for emergency responders, such as on emotions and meaning ( Robinson and Mitchell, 1993 ; Kenardy et al, 1996 ; Chemtob et al, 1997 ; Shalev et al, 1998 ; Regehr and Hill, 2001 ; Tehrani et al, 2001 ; Halpern et al, 2009 ; Palgi et al, 2012 ; Wu et al, 2012 ; Firing et al, 2015 ; Gunasingam et al, 2015 ). Tehrani and colleagues described the group debriefing session delivered to the employees following a response to a rail accident ( Tehrani et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies assessed the impact of non-specific “debriefing”—although the procedures and the focus of the intervention differed between studies. In 11 (58%), debriefing had positive gains for emergency responders, such as on emotions and meaning ( Robinson and Mitchell, 1993 ; Kenardy et al, 1996 ; Chemtob et al, 1997 ; Shalev et al, 1998 ; Regehr and Hill, 2001 ; Tehrani et al, 2001 ; Halpern et al, 2009 ; Palgi et al, 2012 ; Wu et al, 2012 ; Firing et al, 2015 ; Gunasingam et al, 2015 ). Tehrani and colleagues described the group debriefing session delivered to the employees following a response to a rail accident ( Tehrani et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nishi (2012) 35 Randomized controlled trial Japan/high 172 Disaster medical assistance workers (86 fish oil þ psychoeducation, 86 psychoeducation alone)…”
Section: High (2)mentioning
confidence: 99%
“…36 A single RCT by Nishi et al evaluated a pharmacologic intervention, fish oil supplementation, for attenuating posttraumatic stress symptoms. 35 This study assigned rescue workers responding to the Great East Japan earthquake to a group who received fish oil supplementation, as well as psychoeducation versus a group that received psychoeducation alone. This trial found no difference between the 2 groups out of 12 weeks.…”
Section: Personal Summary and Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al conducted an RCT with 2,368 military rescuers 1 month according to the “512 Psychological Intervention Model” and then 1, 2, and 4 months later to follow-up changes in PTSD symptoms, anxiety, and depression based on the DSM-IV criteria. It showed that “512 PIM” was an effective psychological intervention for military rescuers in reducing symptoms of PTSD, anxiety, and depression after this crisis (S. Wu et al, 2012).…”
Section: Treatment Of Ptsd In Wenchuan Earthquake Survivorsmentioning
confidence: 99%